Pengaruh kepemimpinan, Komunikasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT. Iskandar Indah Printing Textile Surakarta - Elsa, Elsa; , Nur Achmad, S.E., M.Si (2015)
The aim of this study was to determine the effect of leadership, communication and working environment on the performance of employees of PT. Iskandar Beautiful Printing Textile Surakarta. This study also aims to determine simultaneously the influence of three independent variables on the dependent variable. Based on the calculation of SPSS 16 o'clock, the validity of test results obtained from the questionnaire data is valid because r_ (count)> r_tabelmaka item is declared valid with an alpha of 0.05, so that all such statements deserve analyzed. Furthermore, the reliability test showed that the Cronbach Alpha reliability coefficient can be unreliable because of> 0.6 then questionnaire data can be trusted. In this study took a sample of 116 employees with simple random sampling of individuals in the population are given an equal opportunity to serve as the research sample. Data types and sources of data used is primary data obtained from the questionnaire answers and secondary data such as archives and literature of the company. Test instrument used in this study was to test the validity and reliability test. Then performed classical assumption that the form of normality test, multicolinearity test and test heterokedastisitas. Significant method, multiple analysis used F test and T test The results showed the influence of leadership and working environment significantly. Of the three variables, variable communication has t_hitung results <t_tabel (0.639 <1.658) then H_o acceptable means no communication influence on employee performance. While the F test obtained value of 6.195 F_hitung> F_tabel (2.68) so that it can be concluded that the independent variables affect the dependent variable (Y) together. Keywords: Employee Performance, Leadership, Communication and Work Environment